(3GdQSGdI GdfbdjIs - (3GdYGedj GdfHWj GdLRjfi, TeS GdOjf, GdTgjO GdChd, eMeO Hf eci Hf eMeO Hf MGeO, J (B786 (3g`s ((3eMeO Ydj GdeGRfOQGfjs)
(3ChdgG (B:s
(3HSe Gddg(B...(3GdMeO ddg GdPj Ve GdfTQ HLeY GdTJGJ hCQSd NjQ GdHTQ HGdHjfGJ(B...(3CeG HYO aEfj deG hbaJ Ydi GdMOjKjf GdeTghQjf Yf Cgd HjJ GdfHhI(B...s
(3BNQgG (B:s
...(3hdjbd aj GdQchY hGdSLhO GdMeO ddg TcQG TcQG hMeOG, hHYO GdJSdje GdMeO ddg GdPj bVi MGLJj hCYWGfj eSCdJj Ke jSLO SLOJj GdTcQ(B...s
(3JHUQI GdYfhGf (B:s
((3GdQSGdI GdfbdjI(B) (3NGJeIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B:(3L(B3(3,U(B731s
(3GdCYdGe(B:(3L(B7(3,U(B109s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis